Indefinite cytomegalovirus prophylaxis with valganciclovir after lung transplantation. Issue 5 (18th July 2019) - Hecker, Matthias; Hecker, Andreas; Askevold, Ingolf; Kuhnert, Stefan; Reichert, Martin; Guth, Stefan; Mayer, Eckhard; Slanina, Heiko; Schüttler, Christian G.; Seeger, Werner; Padberg, Winfried; Mayer, Konstantin
Abstract: Human cytomegalovirus (HCMV) infections and reactivations are common after lung transplantation and are associated with the development of bronchiolitis obliterans syndrome. Against this background, temporary HCMV prophylaxis is an established standard regimen after lung transplantation in most centers. However, the optimal duration of prophylaxis is unclear. We conducted a retrospective two‐center study to determine the efficacy of indefinite lifelong HCMV prophylaxis with oral valganciclovir in a cohort of 133 lung transplant recipients with a mean follow‐up time of approximately 5 years. During the follow‐up period, HCMV DNA was detected in 22 recipients (16.5%). In one case, HCMV pneumonitis developed after prophylaxis had been terminated. We observed a beneficial safety profile and tolerability in our cohort, as the majority of patients still received valganciclovir after a 1‐ and 3‐year observation period, respectively. Compared to the literature, these data indicate a beneficial effect of extended valganciclovir prophylaxis with an acceptable safety profile.